Direito de (não) fumar: uma abordagem humanista - Amanda Flavio de Oliveira (2004)
The impact of tobacco addiction on peoples health and on countries economy has been the object of several researches these days. Their results point to an alarming scenario, and have caused several countries to become concerned about regulating tobacco consumption andproduction. Studies in the sphere of the Law verifying whether it is possible for the State to act in this matter, as well as its limitations, however, are rare. Within the Law area, especially in Brazil, the concern with tobacco addiction has been limited, mainly, to discussions about the possibility to grant compensation to smokers and ex-smokers. One can verify, in these discussions, unjustifiable fixation on smoking myths, which have already been overcome by scientific findings in other areas of human knowledge. This thesis does not intend to be limited to this discussion. Its main objective is to demonstrate the existence of a fundamental right to not smoking, an extension ofthe rights to life and health. Therefore, it becomes an essential task to understand the reality behind myths involving the act of smoking, as well as the true meaning and extent of a govemmental action to control smoking. It is requested, thus, a correct discipline on tobacco addiction, within the Law Science realm. It is believed to be indispensable to study the theme under Economy Law, because it is the most adequate branch of the Law for a just solution. The thesis is philosophically founded upon the Personalism. Derived from Humanism, it considers the human being the maximum value to Science. The humanist conception will also guide the approach method, inspired by the procedures requested by the Annales".